Hybrid solar cooker (International Journal of Engineering and Computer Science, 2017)
This paper addresses that how we can maximize the utilization of solar power for our cooking process. It is done by installing the cooker at some height and its lower or base surface will consist of transparent glass through which sun rays enters into the cooker after getting reflected by the reflecting mirror placed on the ground. This solar cooker also consists of heating element through which cooker gets heated in cloudy weather as well as in night by electricity. Thermostat arrangement is also provided to control the temperature of cooker while running through the electricity.